CEO investment of deferred compensation plans and firm performance. (10th June 2019) - Cambrea, Domenico Rocco; Colonnello, Stefano; Curatola, Giuliano; Fantini, Giulia
Abstract: We study how US chief executive officers (CEOs) invest their deferred compensation plans depending on the firm's profitability. By looking at the correlation between the CEO's return on these plans and the firm's stock return, we show that deferred compensation is to a large extent invested in the company equity in good times and divested from it in bad times. The divestment from company equity in bad times arguably reflects CEOs' incentive to abandon the firm and to invest in alternative instruments to preserve the value of their deferred compensation plans. This result suggests that the incentive alignment effects of deferred compensation crucially depend on the firm's health status.